Comparative Study of Performance Test of Refrigerators and Its Relationship with Electric Power Consumptions - Karudin, Arwizet (Teknomekanik, 2019)
Refrigerator has a significant role as a tool for food storage. Stored foods in refrigerator can be maintain the food quality and delay the stale. Currently, the refrigerator not only used at home but also in offices or shops that sell foods. It could imagine if without refrigerator, the foods will fast stale and lost their quality. This Research aim to know the performance parameters of refrigerator among others consumption total refrigerator power compared to with the resulting performance or Energy Efficiency Ratio (EER), and characteristics decline temperature in cabin at range time certain with two of brands refrigerator on the market. Research about of the refrigerator performances follows ISO-7371-1985 standards, European Standard EN 153, British Standards Institution 1990. Results obtained to refrigerator tested that average input power for refrigerator A is 83.3 Watts and input power inside condition stable of 66 Watts, EER 1.84 and the minimum temperature can be achieved in cabin refrigerator in time for 5 hours; -11.8 ℃ in the above of cabin, -6.2 ℃ in the center of cabin and 5.1 ℃ in the bottom of cabin, temperature product is -14.4 ℃. For refrigerator B average input power is 85.8 Watts and input power inside condition stable is 74 Watts, EER 1.64 and the minimum temperature can be achieved in cabin refrigerator; -5.5 ℃ in the above of cabin, 0.9 ℃ in the middle of cabin and 1.7 ℃, temperature product is -9.8 ℃.